La dramatización en el desarrollo sociocomunicacional en estudiantes de noveno año, "Unidad Educativa Ciudad de Machala", periodo 2023-2024. - Sánchez Vargas, Yomira Alexandra; Rivera Alvarado, Julissa Ximena (Machala: Universidad Técnica de Machala, 2024)
The present research work entitled Dramatization in the socio-communicative development of ninth year students in the educational unit City of Machala, period 2023-2024, is oriented to the search and analysis of information on dramatization in socio-communicative development, because at present in the classroom the participation of students is not encouraged and this is reflected in the lack of skills they have to communicate when presenting themselves to society. In order to determine the impact of dramatisation in the socio-communicative development of ninth year students, educational unit Ciudad de Machala, period 2023- 2024. The methodology of this approach is quantitative and qualitative, by virtue of the analysis carried out through scientific journals, using interviews and surveys as data collection techniques. In the first one, 5 teachers were interviewed through open questions, then 99 students were surveyed in which the survey of closed questions was applied. As a result, the respective tabulations were made in the statistical tables and as far as the type of research is concerned, it is of a documentary and field nature. The results obtained on the basis of the instruments applied showed that students do not participate in cooperative group practices or oral presentations and therefore have a low level of socio-emotional development. In the context, it was identified that teachers do not use strategies such as dramatization for the development of creativity, which limits their ability to implement it during class hours. In summary, the difficulties to be able to develop dramatization in the classroom are limited due to this a proposal has been developed Video tutorial for the design and implementation of dramatization as a didactic strategy for socio-communicative development in ninth year students of the educational unit Ciudad de Machala. In which you will learn about the definition, characteristics, elements, methodological process and the application of dramatization within the educational environment for a more dynamic education. In conclusion, drama is an essential strategy for developing empathy, active listening, cooperation and emotional expression because it allows students to put themselves in the place of others by understanding that their perspectives and reality are different. By participating in drama classes, students develop active listening skills because they must pay attention to their peers in order to construct a coherent and effective story. In addition, drama promotes collaboration because students must work together to create and perform scenes, which helps to increase the sense of community and collaboration in the classroom.
El presente trabajo investigativo titulado La dramatización en el desarrollo sociocomunicacional en los estudiantes de noveno año unidad educativa Ciudad de Machala, periodo 2023-2024, está orientado a la búsqueda y análisis de la información sobre la dramatización en el desarrollo sociocomunicacional, en virtud a que en la actualidad en las aulas no se fomenta la participación de los estudiantes y esto se ve reflejado en la falta de habilidades que tienen para comunicarse al momento de presentarse ante la sociedad. Con la finalidad de determinar la incidencia de la dramatización en el desarrollo socio-comunicacional en estudiantes de noveno año, unidad educativa Ciudad de Machala, periodo 2023- 2024. En cuanto a la metodología de este enfoque es cuantitativo y cualitativo, en virtud al análisis que se realizó mediante revistas científicas usándose como técnica de recolección de datos la entrevista y encuesta. En la primera fueron entrevistados 5 docentes a través de preguntas abiertas, luego se encuesto a 99 estudiantes en el cual se aplicó la encuesta de preguntas cerradas. Como resultado se realizaron las respectivas tabulaciones en los cuadros estadísticos y en lo que respecta a tipo de investigación es de carácter documental y de campo. Los resultados obtenidos en base a los instrumentos aplicados se pudieron evidenciar que los estudiantes no participan en prácticas de grupos cooperativos ni exposiciones orales por consiguiente tienen un bajo nivel de desarrollo socioemocional. Siguiendo con el contexto, se identificó que los docentes no utilizan estrategias como la dramatización para el desarrollo de la creatividad, lo que limita su capacidad para implementarlo, durante sus horas de clase. En resumen, las dificultades para poder desarrollar la dramatización en el aula de clases son limitadas debido a esto se ha desarrollado una propuesta Video tutorial para el diseño e implementación de la dramatización como estrategia didáctica para el desarrollo sociocomunicacional en los estudiantes de noveno año de la unidad educativa Ciudad de Machala. En el cual se aprenderá sobre la definición, características, elementos, proceso metodológico y la aplicación de la dramatización dentro del entorno educativo para una educación más dinámica.
Keywords: DRAMATIZACION; SOCIOCOMUNICACIONAL; EXPRESION; PARTICIPACION